The Ethics of Pre-Implantation Genetic Diagnosis in Practice: An Analysis of the Feasibility and Ethical Considerations of Applying and Regulating Genetic Enhancement - Bleeker, Helena (Université d'Ottawa | University of Ottawa, 2013)
Pre-Implantation genetic diagnosis (PGD) has many therapeutic and enhancement applications. In a previous work, I presented arguments in favour of all types of PGD, whether for medical therapies or human enhancement. These arguments were based on the absence of moral distinctions between genetic therapy and genetic enhancement. The implication of these arguments is that, if one cannot distinguish between therapy and enhancement on moral grounds, then all PGD applications must be either moral or immoral. Although logically speaking this argument may be true, in practice I believe that it is possible and necessary to draw a line between what is morally permissible and what is not with respect to applications of PGD for genetic enhancement. In order to draw this line, I move away from analyzing the moral substance of PGD as a technology and focus instead on the moral agents that will employ PGD. As humans, I believe we are both morally accountable and morally unreliable as agents for the use of PGD, and this feature forms the basis of the delineation of acceptable PGD practices.
Keywords: Bioethics; In vitro fertilization; Pre-implantation genetic diagnosis; Genetic enhancement; Bioliberalism